Vacuum assisted closure versus total contact casting in the healing of plantar foot ulcers: a comparative prospective study - Challapalli, Srikanth Reddy; Peddavenkatagari, Theja; Sukanya, Chanda; Gandikota, Venkataprakash; Srimanthula Venkata, Praveena; Potluri, Bharathi (International Surgery Journal, 2019)
Background: The objective of the study was to compare the effectiveness of vacuum assisted closure (VAC) and total contact casting (TCC) in the healing of plantar foot ulcers. Chronic leg ulcers are a significant cause of morbidity in developing countries like India, leading to excessive health care expenses and loss of effective work hours, inspite of availability of various novel modalities of management. This study aims to compare the effectiveness of vacuum assisted closure and total contact casting in the healing in plantar foot ulcers, in order to standardise a procedure with maximum benefits. Methods: This comparative prospective study was conducted on 150 individuals admitted to SVRRGG Hospital, Tirupati, with the diagnosis of plantar foot ulcers from august 2017 to march 2019. They were divided into 2 groups, Group A (75 patients treated with VAC) and Group B (75 patients treated with TCC). In this study, the outcomes assessed were reduction of wound size and length of hospital stay. Results: In this study, mean reduction of wound surface area with VAC and TCC was 21.09 and 12.83 respectively, mean percentage of reduction of wound size with VAC is 90.43 and in TCC was 52.36. Mean hospital stay with VAC and TCC was 24.90 days and 51.29 days respectively. Conclusions: VAC is more effective than TCC in the treatment of foot ulcers, with less duration of hospital stay and earlier returns to work.